Artificial Intelligence Affordances for Organisational Change: Perspectives from South African Artificial Intelligence Practitioners - Achmat, Luqman (Department of Information Systems, 2024)
Artificial intelligence (AI) technologies have been in use for several decades, but have seen substantial growth and commercialisation in the last decade, largely due to the available and growing ubiquitous access to more affordable computing resources. While some organisations have adopted these technologies fairly quickly, others grapple with understanding how these technologies would strategically benefit the organisation. The purpose of this research is to address this gap by theorising how AI could be positioned to influence strategic organisational change. It does so by delineating the AI features and drawing on affordance theory to explicitly identify the affordances, the types of organisational change and the constraining conditions under which such AI-related affordances may influence organisational change. This qualitative study adopts an interpretive epistemology, while lending itself towards a constructivist ontology. By adopting a qualitative interview strategy for data collection, and a thematic analysis to analyse the data, this study abductively theorises how AI affords organisational change from the perspective of the AI practitioner. It uses the Trajectory of Affordances as the underpinning lens to explore this phenomenon. Eight key affordances are identified: (i) Analysing risk, (ii) analysing needs, (iii) forecasting, (iv) assessing efficiency and effectiveness, (v) providing prediction criteria, (vi) translating information, (vii) tailoring information, and (viii) improving predictability as an affordance that results from an outcome or organisational change influenced by one or more of the other affordances.